A Study of Possible Crop Combinations in Vegetable Intercropping System With Cabbage (Brassica Oleracea Var. Capitata) as the Base Crop - Nik Mat, Nik Aziz (1985)
The biological and econamic advantages of intercropping chilli (Capsicum annum), okra (Abelmoschus esculentus) and long bean (Vigna sesquipedalis fruw) with cabbage (Brassica oleracea var. capitata) at three different planting intervals were assessed by Iand quivalent Ratio (LER), Area Time equivalent Ratio (ATER), Relative Value Total (RVT) am gross marqin. the effect of intercropping on yield am other horticultural characteristics of both cabbage am the component crops were also assessed. Results obtained. showed that chilli + cabbage, okra + cabbage and long bean + cabbage intercrop canbinations overyielded biologically am eronanically as beth the LER and RVT of each of these intercrop conbinations was greater than one.